Aerated concrete block for purifying indoor air and preparation method thereof
By using a purified indoor air aerated concrete block made of raw materials such as titanium gypsum, combined with lightweight materials and modified activated carbon, the problem of poor combination of lightweight materials and air purification functions in the existing technology is solved, and efficient indoor air purification and solid waste resource utilization is achieved.
Patent Information
- Application Number
- CN202310602762.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-05-26
AI Technical Summary
The prior art is difficult to effectively combine lightweight materials with air purification functions, and the existing air purification technology has high production costs and average purification efficiency.
A purified indoor air aerated concrete block is made of raw materials such as titanium gypsum, silicate cement, aluminate cement, quicklime, fly ash, aluminum powder, quartz sand, coconut charcoal, modified activated carbon, etc., and through specific preparation methods and process flows, a material with good mechanical properties and efficient adsorption of VOCs is formed.
It has achieved efficient purification of indoor air, good mechanical properties and adsorption capabilities, and can realize the reduction and resource utilization of solid waste, reducing the pollution of solid waste accumulation to the environment.
Smart Images

Figure CN116514516B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wall materials, and in particular to an indoor air purifying aerated concrete building block and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of my country's economy, the indoor environment where people live and work has undergone tremendous changes. Closed decoration and the decorative materials used in the interior cause indoor air pollution. Common indoor pollutants include: volatile gas pollutants such as formaldehyde, benzene, ammonia, microbial pollutants such as bacteria and viruses, and particulate matter. Indoor air pollution first harms the respiratory tract. In addition to causing "building syndrome", it can also cause or aggravate subchronic and chronic respiratory diseases such as bronchitis, allergic pneumonia, lung cancer and other organ cancers. The problem of indoor air pollution has attracted great attention from people. In recent years, some air purification facilities have gradually been used in offices, schools, shopping malls, hospitals and residential places to reduce the harm of indoor air pollutants to the human body and improve the office and living environment.
[0003] At present, the indoor air purification technologies in the market are mainly divided into two categories: physical methods and chemical methods. Physical methods include mechanical filtration, adsorption purification, electrostatic filtration, etc. Chemical methods are more about using certain specific methods to generate free radicals with strong oxidizing properties or using chemical agents to remove toxic and harmful gases and microorganisms through chemical reactions, such as plasma purification, photocatalytic purification, hypochlorous acid, hydrogen peroxide disinfection, etc.
[0004] As an emerging material, lightweight materials are highly praised by countries around the world for their unique lightness, sound absorption and heat insulation. At present, lightweight materials are mostly used in house partition boards, etc., only for sound absorption and heat insulation, and have not been combined with purification of indoor harmful gases. To combine lightweight materials with purification of indoor harmful gases to prepare lightweight indoor air purification materials, it is necessary to combine lightweight blocks with coconut fiber charcoal. Coconut fiber charcoal as a lightweight skeleton can produce lightweight indoor air purification materials that have both sound absorption and heat insulation properties and harmful gas purification properties. However, if the amount of coconut fiber charcoal added is too low, the adsorption capacity is limited. If it is added too much, the strength performance of the material will be reduced.
[0005] Chinese patent application CN112125598A proposes a method for preparing autoclaved aerated concrete based on titanium gypsum, which uses a large amount of titanium gypsum to prepare low-cost, high-strength autoclaved aerated concrete blocks. This invention can promote the resource utilization rate of titanium gypsum, create practical value, and broaden the source of raw materials for autoclaved concrete. However, this invention does not mention the use of autoclaved concrete combined with certain active substances to purify the air.
[0006] Chinese patent application CN113736293A proposes an environmentally friendly wall coating for construction and its preparation method, which uses glue powder, silicone gel, nano-montmorillonite composite powder, diatomaceous earth dispersion, nano calcium silicate, nano titanium dioxide, glass fiber powder, red clay, lime, water, lignin, acrylamide, bamboo charcoal powder, alfalfa powder, tobacco straw fiber powder, Chuanxiong extract, Patchouli extract, mint extract and natural plant essential oil to prepare wall materials, which can not only purify indoor air, but also have the functions of heat preservation, heat insulation and fire prevention. This invention is conducive to the purification of indoor air. However, this invention has high production cost and general purification efficiency. Summary of the invention
[0007] The purpose of the present invention is to propose an aerated concrete block for purifying indoor air and a preparation method thereof. The preparation method is simple and the raw materials are widely available. The prepared aerated concrete block for purifying indoor air has good mechanical properties, VOCs adsorption capacity, and formaldehyde purification capacity. It can also achieve the reduction and resource utilization of solid waste, thereby reducing the pollution of the environment caused by the accumulation of solid waste.
[0008] The technical solution of the present invention is achieved in this way:
[0009] The invention provides an indoor air purifying aerated concrete block, which is prepared from the following raw materials by weight: 10-40 parts of titanium gypsum, 10-20 parts of silicate cement, 2-10 parts of aluminate cement, 10-20 parts of quicklime, 20-60 parts of fly ash, 1-2 parts of aluminum powder, 5-20 parts of quartz sand, 0.5-10 parts of coconut fiber carbon, 0.5-2 parts of foam stabilizer, 0.2-2 parts of water reducer, 40-45 parts of water, and 5-10 parts of modified activated carbon. The content of coconut fiber carbon is preferably 3-5 parts.
[0010] As a further improvement of the present invention, the foam stabilizer is selected from one or more of polyacrylamide, polyvinyl alcohol, sodium sulfate of fatty alcohol polyoxyethylene ether, dodecyl dimethyl amine oxide, and alkyl alcohol amide; the water reducer is selected from one or more of naphthalene water reducer, aliphatic water reducer, amino water reducer, and polycarboxylic acid water reducer. The aluminum powder is also called aerated aluminum powder.
[0011] As a further improvement of the present invention, the modified activated carbon is wrinkled graphene-coated TiO2@activated carbon.
[0012] As a further improvement of the present invention, the preparation method of the wrinkled graphene-coated TiO2@activated carbon is as follows:
[0013] S1. Soaking the activated carbon in an alkali solution, filtering, washing, drying, and ball milling to obtain a pretreated activated carbon powder;
[0014] S2. The tetrabutyl titanate, ethanol and water are mixed to obtain a titanium sol;
[0015] S3. The pretreated activated carbon powder obtained in step S1 is added to the titanium sol obtained in step S2, stirred and mixed evenly, calcined, and ball-milled to obtain TiO2@activated carbon;
[0016] S4. The TiO2@activated carbon obtained in step S3 is added to the graphene oxide aqueous solution, stirred and mixed evenly, and spray-dried to obtain wrinkled graphene oxide-coated TiO2@activated carbon;
[0017] S5. Add the wrinkled graphene oxide coated TiO2@activated carbon obtained in step S4 into water, add ammonia water and hydrazine hydrate, heat and stir to react, filter, wash, and dry to obtain wrinkled graphene coated TiO2@activated carbon.
[0018] As a further improvement of the present invention, the alkali solution in step S1 is a 5-10wt% NaOH or KOH solution, the solid-liquid ratio of the activated carbon and the alkali solution is 1:5-10g / mL, and the ball milling time is 2-4h; the mass ratio of tetrabutyl titanate, ethanol and water in step S2 is 10-15:70-100:7-12.
[0019] As a further improvement of the present invention, in step S3, the mass ratio of the pretreated activated carbon powder to the titanium sol is 10:12-15, the calcination temperature is 400-500°C, the time is 2-4h, and the ball milling time is 1-2h.
[0020] As a further improvement of the present invention, the concentration of graphene oxide in the graphene oxide aqueous solution in step S4 is 10-15wt%, the mass ratio of the TiO2@activated carbon and the graphene oxide aqueous solution is 1:5-10, and the conditions for the spray drying are an inlet air temperature of 80-100°C, an outlet air temperature of 30-80°C, and an evaporated water amount of 1500-2000mL / h.
[0021] As a further improvement of the present invention, in step S5, the mass ratio of the wrinkled graphene oxide coated TiO2@activated carbon, ammonia water and hydrazine hydrate is 10:3-5:1-3, the concentration of ammonia water is 25-27wt%, the temperature of the heating and stirring reaction is 75-85°C, and the time is 1-2h.
[0022] The present invention further protects a method for preparing the above-mentioned indoor air purifying aerated concrete block, comprising the following steps:
[0023] 1) Mixing silicate cement, aluminate cement, quicklime, fly ash, modified activated carbon and quartz sand uniformly to obtain powder;
[0024] 2) mixing aluminum powder and 1-2 parts of water and then ultrasonically mixing to obtain a suspension 1;
[0025] 3) mixing titanium gypsum and 20-30 parts of water and wet grinding to obtain slurry 1;
[0026] 4) adding the powder, slurry 1, water reducing agent and remaining water into a blender and stirring to obtain slurry 2;
[0027] 5) adding the suspension 1, the foam stabilizer and the coconut fiber charcoal into the slurry 2 and continuing to stir and mix in a blender to obtain a slurry 3;
[0028] 6) injecting the slurry 3 into a mold for forming, curing in a curing box, demoulding, and continuing curing for a specified time, and then placing the hardened body into a cement autoclave to obtain a porous lightweight material;
[0029] 7) piling the aerated concrete blocks into a wall, and applying a layer of environmentally friendly water-based paint on the surface of the wall to obtain aerated concrete blocks for purifying indoor air.
[0030] The present invention further protects a method for preparing the above-mentioned indoor air purifying aerated concrete block, comprising the following steps:
[0031] 1) Mixing silicate cement, aluminate cement, quicklime, fly ash, wrinkled graphene-coated TiO2@activated carbon and quartz sand to obtain powder;
[0032] 2) mixing aluminum powder and 1-2 parts of water and then ultrasonically mixing to obtain a suspension 1;
[0033] 3) mixing titanium gypsum and 20-30 parts of water and wet grinding to obtain slurry 1;
[0034] 4) adding the powder, slurry 1, water reducing agent and remaining water into a blender and stirring to obtain slurry 2;
[0035] 5) adding the suspension 1, the foam stabilizer and the coconut fiber charcoal into the slurry 2 and continuing to stir and mix in a blender to obtain a slurry 3;
[0036] 6) injecting the slurry 3 into a mold for forming, curing in a curing box, demoulding, and continuing curing for a specified time, and then placing the hardened body into a cement autoclave to obtain a porous lightweight material;
[0037] 7) piling the aerated concrete blocks into a wall, and applying a layer of environmentally friendly water-based paint on the surface of the wall to obtain aerated concrete blocks for purifying indoor air.
[0038] The prepared lightweight material needs to be autoclaved and cured (170-200°C) in a cement autoclave for 5-10 hours, with an apparent porosity of more than 80% and a strength that meets the requirements of A3.0 B06 in GB / T 11968-2020.
[0039] The mold needs to be preheated at 50-70℃ in advance. The pre-curing conditions are humidity ≥70% and temperature ≥50℃. The steam curing conditions are temperature 170-200℃ and time 5-10h. The pore size of the lightweight material is 0.01-2mm. The adsorption efficiency of harmful gases such as formaldehyde can reach 90% (based on 300m3 indoor space).
[0040] The present invention has the following beneficial effects:
[0041] The present invention prepares a wrinkled graphene-coated TiO2@activated carbon. The pore structure of the activated carbon determines the adsorption performance of the activated carbon. The activated carbon itself has no polarity and its surface is hydrophobic. The carbon surface is easily oxidized by an oxidant or reduced by a reducing agent, so that a variety of functional groups are generated on its surface. After being treated with alkali solution, a large number of hydroxyl structures are formed on the surface, so that the titanium sol prepared by the sol-gel reaction is easily deposited on the surface. After calcination, TiO2@activated carbon is formed, and added to an aqueous solution of graphene oxide. Through the action of hydrogen bonding, the graphene oxide is coated on the surface of the TiO2@activated carbon. The activated carbon passes through a nozzle under the action of air pressure and is broken into small droplets containing solid particles, which enter a cyclone separator together with heated nitrogen. In this process, the solvent evaporates rapidly, resulting in a volume shrinkage of the droplets. After cyclone separation, wrinkled graphene oxide TiO2@activated carbon microspheres can be obtained, and after further reduction, wrinkled graphene-coated TiO2@activated carbon can be obtained;
[0042] The wrinkled graphene-coated TiO2@activated carbon prepared by the present invention can effectively reduce the stacking of the coated TiO2@activated carbon in the material, avoid agglomeration caused by the ordered structure of the coated TiO2@activated carbon, achieve uniform dispersion, and give full play to the excellent performance of graphene and TiO2@activated carbon. On the one hand, the pore structure of TiO2@activated carbon is improved, and on the other hand, the mechanical properties, VOCs adsorption capacity, formaldehyde purification capacity, etc. of the wall material are significantly improved, and the mechanical properties caused by coconut fiber carbon can be compensated.
[0043] The present invention also utilizes the light weight and high adsorption of coconut fiber charcoal to achieve the adsorption of harmful gases and achieve the purpose of indoor air purification. The adsorption efficiency of harmful gases such as formaldehyde can reach 90%. In addition, lightweight materials are prepared from a variety of solid wastes to achieve solid waste reduction and resource utilization, thereby reducing the pollution of solid waste accumulation to the environment.
[0044] The indoor air purifying aerated concrete building block prepared by the present invention has a simple preparation method and a wide source of raw materials. The prepared indoor air purifying aerated concrete building block has good mechanical properties, VOCs adsorption capacity, and formaldehyde purification capacity, and can also achieve solid waste reduction and resource utilization, thereby reducing the pollution of solid waste accumulation to the environment. The performance of the prepared indoor air purifying aerated concrete building block meets the A3.5 B06 standard, has long-term volume stability, and has good adsorption stability and high adsorption efficiency for harmful gases such as formaldehyde. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0046] Figure 1 This is a schematic diagram of an aerated concrete block for purifying indoor air prepared in Example 1 of the present invention;
[0047] Figure 2 This is the SEM image of the wrinkled graphene-coated TiO2@activated carbon prepared in Preparation Example 1 of the present invention. DETAILED DESCRIPTION
[0048] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] The chemical composition of the titanium gypsum raw material described in the following examples is CaO: 20%-30%, SO3: 20%-30%, Fe2O3: 5%-10%, SiO2: 2%-5%, Al2O3: 2%-5%. The compressive strength of the autoclaved aerated concrete block is determined according to the national standard GB / T 11969-2020 "Autoclaved Aerated Concrete Performance Test Method".
[0050] Graphene oxide is commercially available or can be prepared using a modified Hummers method:
[0051] Step 1, weigh 10g of natural graphite powder (G), 4g of potassium persulfate, and 10g of phosphorus pentoxide, add them into a three-necked flask containing 24mL of sulfuric acid while stirring, first react in a constant temperature water bath at 60°C for 3h, then move the three-necked flask into a constant temperature water bath at 25°C for 5h, filter, wash with deionized water to neutrality, and dry in air to obtain pre-oxidized graphite (PG);
[0052] Step 2: Weigh 1g of pre-oxidized graphite, add it to a three-necked flask with 25mL of sulfuric acid while stirring, put it in an ice-water bath, and after the pre-oxidized graphite is completely dissolved, add 3g of potassium permanganate, react for 2h, then move the three-necked flask into a constant temperature water bath at 35°C to react for 40min, finally add deionized water, continue to react at 35°C for 1h, and finally add 30% H2O2 until no more gas is generated and the solution turns bright yellow. Centrifuge and filter while hot, and wash with 5% hydrochloric acid and deionized water until neutral. After the final precipitate is ultrasonically shaken at 1000W for 1h, pour it into a culture dish and dry it at 90°C for 24h to obtain flaky graphite oxide (GO).
[0053] Portland cement, 42.5r, purchased from Henan Hao Nai Building Materials Co., Ltd.; aluminate cement purchased from Jianai Special Aluminate Co., Ltd., model is CA50-A700, compressive strength 62-80MPa; quartz sand is standard sand, purchased from Xiamen Ace Standard Sand Co., Ltd.; coconut fiber carbon, particle size is 20-10 mesh, water content <10%, purchased from Hebei Boyuan Activated Carbon Manufacturing Co., Ltd. The water reducer is a polycarboxylic acid water reducer purchased from Shandong Huayunda New Materials Co., Ltd.
[0054] Preparation Example 1
[0055] The preparation method of wrinkled graphene coated TiO2@activated carbon is as follows:
[0056] S1. The activated carbon was immersed in a 5wt% NaOH solution, the solid-liquid ratio of the activated carbon to the alkali solution was 1:5g / mL, filtered, washed, dried, and ball-milled for 2h to obtain a pretreated activated carbon powder;
[0057] S2. 10 parts by weight of tetrabutyl titanate, 70 parts by weight of ethanol and 7 parts by weight of water were mixed to obtain a titanium sol;
[0058] S3. 10 parts by weight of the pretreated activated carbon powder obtained in step S1 was added to 12 parts by weight of the titanium sol obtained in step S2, stirred and mixed, calcined at 400 ° C for 2h, ball milled for 1h to obtain TiO2 @ activated carbon;
[0059] S4. 10 parts by weight of the TiO2@ activated carbon obtained in step S3 were added to 50 parts by weight of a 10wt% aqueous solution of graphene oxide, stirred and mixed, and spray-dried to obtain wrinkled graphene oxide-coated TiO2@ activated carbon;
[0060] The spray drying conditions were an inlet air temperature of 80°C and an outlet air temperature of 40°C;
[0061] S5. Add 10 parts by weight of the wrinkled graphene oxide coated TiO2@activated carbon obtained in step S4 into water, add 3 parts by weight of 25wt% ammonia water and 1 part by weight of hydrazine hydrate, heat to 75°C, stir the reaction for 1 hour, filter, wash, and dry to obtain wrinkled graphene coated TiO2@activated carbon. Figure 2 This is the SEM image of the wrinkled graphene-coated TiO2@activated carbon. It can be seen from the figure that a wrinkled structure is formed on the surface.
[0062] Preparation Example 2
[0063] The preparation method of wrinkled graphene coated TiO2@activated carbon is as follows:
[0064] S1. The activated carbon was immersed in a 10wt% KOH solution, the solid-liquid ratio of the activated carbon to the alkali solution was 1:10g / mL, filtered, washed, dried, and ball-milled for 4h to obtain a pretreated activated carbon powder;
[0065] S2. 15 parts by weight of tetrabutyl titanate, 100 parts by weight of ethanol and 12 parts by weight of water were mixed to obtain a titanium sol;
[0066] S3. 10 parts by weight of the pretreated activated carbon powder obtained in step S1 was added to 15 parts by weight of the titanium sol obtained in step S2, stirred and mixed, calcined at 500 ° C for 4h, ball milled for 2h to obtain TiO2 @ activated carbon;
[0067] S4. 10 parts by weight of the TiO2@ activated carbon obtained in step S3 were added to 100 parts by weight of a 15wt% aqueous solution of graphene oxide, stirred and mixed, and spray-dried to obtain wrinkled graphene oxide-coated TiO2@ activated carbon;
[0068] The spray drying conditions were an inlet air temperature of 100°C and an outlet air temperature of 50°C;
[0069] S5. Add 10 parts by weight of the wrinkled graphene oxide coated TiO2@activated carbon obtained in step S4 into water, add 5 parts by weight of 27wt% ammonia water and 3 parts by weight of hydrazine hydrate, heat to 85°C, stir and react for 2h, filter, wash, and dry to obtain wrinkled graphene coated TiO2@activated carbon.
[0070] Preparation Example 3
[0071] The preparation method of wrinkled graphene coated TiO2@activated carbon is as follows:
[0072] S1. The activated carbon was immersed in a 7wt% NaOH solution, the solid-liquid ratio of the activated carbon to the alkali solution was 1:7g / mL, filtered, washed, dried, and ball-milled for 3h to obtain a pretreated activated carbon powder;
[0073] S2. 12 parts by weight of tetrabutyl titanate, 85 parts by weight of ethanol and 10 parts by weight of water were mixed to obtain a titanium sol;
[0074] S3. 10 parts by weight of the pretreated activated carbon powder obtained in step S1 was added to 13.5 parts by weight of the titanium sol obtained in step S2, stirred and mixed, calcined at 450 ° C for 3h, ball milled for 1.5h to obtain TiO2@ activated carbon;
[0075] S4. 10 parts by weight of the TiO2@ activated carbon obtained in step S3 was added to 70 parts by weight of a 12wt% aqueous solution of graphene oxide, stirred and mixed, and spray-dried to obtain wrinkled graphene oxide-coated TiO2@ activated carbon;
[0076] The spray drying conditions were an inlet air temperature of 90°C and an outlet air temperature of 50°C;
[0077] S5. Add 10 parts by weight of the wrinkled graphene oxide coated TiO2@activated carbon obtained in step S4 into water, add 4 parts by weight of 26wt% ammonia water and 2 parts by weight of hydrazine hydrate, heat to 80°C, stir and react for 1.5h, filter, wash, and dry to obtain wrinkled graphene coated TiO2@activated carbon.
[0078] Comparative Preparation Example 1
[0079] Compared with Preparation Example 3, the difference is that steps S2 and S3 in Preparation Example 3 are not performed.
[0080] Instead, the following preparation method is used:
[0081] S1. The activated carbon was immersed in a 7wt% NaOH solution, the solid-liquid ratio of the activated carbon to the alkali solution was 1:7g / mL, filtered, washed, dried, and ball-milled for 3h to obtain a pretreated activated carbon powder;
[0082] S2. Add 10 parts by weight of the pretreated activated carbon powder obtained in step S1 to 70 parts by weight of a 12wt% aqueous solution of graphene oxide, stir and mix evenly, and spray dry to obtain wrinkled graphene oxide-coated activated carbon;
[0083] The spray drying conditions were an inlet air temperature of 90°C and an outlet air temperature of 50°C;
[0084] S3. Add 10 parts by weight of the wrinkled graphene oxide coated activated carbon obtained in step S2 into water, add 4 parts by weight of 26wt% ammonia water and 2 parts by weight of hydrazine hydrate, heat to 80°C, stir the reaction for 1.5h, filter, wash, and dry to obtain wrinkled graphene coated activated carbon.
[0085] Comparative Preparation Example 2
[0086] Compared with Preparation Example 3, the difference is that step S1 in Preparation Example 3 is not performed.
[0087] Instead, the following preparation method is used:
[0088] S1. 12 parts by weight of tetrabutyl titanate, 85 parts by weight of ethanol and 10 parts by weight of water were mixed to obtain a titanium sol;
[0089] S2. 10 parts by weight of activated carbon powder was added to 13.5 parts by weight of the titanium sol obtained in step S2, stirred and mixed, calcined at 450 ° C for 3h, ball milled for 1.5h to obtain TiO2 @ activated carbon;
[0090] S3. 10 parts by weight of the TiO2@ activated carbon obtained in step S2 was added to 70 parts by weight of a 12wt% aqueous solution of graphene oxide, stirred and mixed, and spray-dried to obtain wrinkled graphene oxide-coated TiO2@ activated carbon;
[0091] The spray drying conditions were an inlet air temperature of 90°C and an outlet air temperature of 50°C;
[0092] S4. Add 10 parts by weight of the wrinkled graphene oxide coated TiO2@activated carbon obtained in step S3 into water, add 4 parts by weight of 26wt% ammonia water and 2 parts by weight of hydrazine hydrate, heat to 80°C, stir and react for 1.5h, filter, wash, and dry to obtain wrinkled graphene coated TiO2@activated carbon.
[0093] Comparative Preparation Example 3
[0094] Compared with Preparation Example 3, the difference is that steps S4 and S5 in Preparation Example 3 are not performed.
[0095] Instead, the following preparation method is used:
[0096] S1. The activated carbon was immersed in a 7wt% NaOH solution, the solid-liquid ratio of the activated carbon to the alkali solution was 1:7g / mL, filtered, washed, dried, and ball-milled for 3h to obtain a pretreated activated carbon powder;
[0097] S2. 12 parts by weight of tetrabutyl titanate, 85 parts by weight of ethanol and 10 parts by weight of water were mixed to obtain a titanium sol;
[0098] S3. Add 10 parts by weight of the pretreated activated carbon powder obtained in step S1 to 13.5 parts by weight of the titanium sol obtained in step S2, stir and mix evenly, calcine at 450°C for 3h, and ball mill for 1.5h to obtain TiO2@activated carbon.
[0099] Comparative Preparation Example 4
[0100] Compared with Preparation Example 3, the difference is that step S5 in Preparation Example 3 is not performed.
[0101] Instead, the following preparation method is used:
[0102] S1. The activated carbon was immersed in a 7wt% NaOH solution, the solid-liquid ratio of the activated carbon to the alkali solution was 1:7g / mL, filtered, washed, dried, and ball-milled for 3h to obtain a pretreated activated carbon powder;
[0103] S2. 12 parts by weight of tetrabutyl titanate, 85 parts by weight of ethanol and 10 parts by weight of water were mixed to obtain a titanium sol;
[0104] S3. 10 parts by weight of the pretreated activated carbon powder obtained in step S1 was added to 13.5 parts by weight of the titanium sol obtained in step S2, stirred and mixed, calcined at 450 ° C for 3h, ball milled for 1.5h to obtain TiO2@ activated carbon;
[0105] S4. 10 parts by weight of the TiO2@ activated carbon obtained in step S3 was added to 70 parts by weight of a 12wt% aqueous solution of graphene oxide, stirred and mixed, and spray-dried to obtain wrinkled graphene oxide-coated TiO2@ activated carbon;
[0106] The spray drying conditions were as follows: the inlet air temperature was 90°C and the outlet air temperature was 50°C.
[0107] Example 1
[0108] This embodiment provides an aerated concrete block for purifying indoor air.
[0109] Raw material composition (parts by weight): 10 parts of titanium gypsum, 10 parts of silicate cement, 2 parts of aluminate cement, 10 parts of quicklime, 20 parts of fly ash, 1 part of aluminum powder, 5 parts of quartz sand, 3 parts of coconut fiber charcoal, 0.5 parts of foam stabilizer dodecyl dimethyl amine oxide, 0.2 parts of water reducer, 40 parts of water, 5 parts by weight of wrinkled graphene-coated TiO2@activated carbon prepared in Preparation Example 1.
[0110] The preparation method is as follows:
[0111] (1) drying silicate cement, aluminate cement, quicklime, fly ash, wrinkled graphene-coated TiO2@activated carbon and quartz sand at 105° C. and mixing them uniformly to obtain a powder;
[0112] (2) After mixing aerated aluminum powder with 2 parts of water, ultrasonically disperse the mixture for 60 seconds to obtain suspension 1;
[0113] (3) The titanium gypsum is crushed and mixed with 20 parts of water, and then wet-milled using a planetary ball mill so that all the slurry passes through a 120-mesh sieve to obtain slurry 1; the water reducer is mixed with 2 parts of water and set aside, and the foam stabilizer is weighed and set aside to obtain.
[0114] (4) adding the uniformly mixed powder, slurry 1, water reducing agent and remaining water into a blender and stirring for 50 seconds to obtain slurry 2;
[0115] (5) adding the suspension 1, the foam stabilizer and the coconut fiber charcoal to the slurry 2 and continuing to stir and mix in a blender to obtain a slurry 3;
[0116] (6) Pour slurry 3 into a mold preheated at 60° C., and place it in a curing box with a humidity of ≥70% and a temperature of 70° C. for curing for 1 day. After the curing is completed, cut off the bread head and demould, and then place it in a cement autoclave at a temperature of 200° C. for autoclave curing for 8 hours. After taking it out of the autoclave, the required lightweight materials are obtained. Qualified lightweight materials are selected and piled into walls. A layer of environmentally friendly water-based paint is brushed on the surface of the wall to obtain indoor air-purifying aerated concrete blocks. Figure 1 Schematic diagram of the prepared aerated concrete block for purifying indoor air.
[0117] Example 2
[0118] This embodiment provides an aerated concrete block for purifying indoor air.
[0119] Raw material composition (parts by weight): 40 parts of titanium gypsum, 20 parts of silicate cement, 10 parts of aluminate cement, 20 parts of quicklime, 60 parts of fly ash, 2 parts of aerated aluminum powder, 20 parts of quartz sand, 5 parts of coconut fiber charcoal, 2 parts of foam stabilizer dodecyl dimethyl amine oxide, 2 parts of water reducer, 45 parts of water, 10 parts by weight of wrinkled graphene-coated TiO2@activated carbon prepared in Preparation Example 1.
[0120] Other experimental steps and conditions are the same as those in Example 1.
[0121] Example 3
[0122] This embodiment provides an aerated concrete block for purifying indoor air.
[0123] Raw material composition (parts by weight): 25 parts of titanium gypsum, 15 parts of silicate cement, 7 parts of aluminate cement, 15 parts of quicklime, 40 parts of fly ash, 2 parts of aerated aluminum powder, 12 parts of quartz sand, 5 parts of coconut fiber charcoal, 1 part of foam stabilizer dodecyl dimethyl amine oxide, 1 part of water reducer, 42 parts of water, 7 parts by weight of wrinkled graphene-coated TiO2@activated carbon prepared in Preparation Example 1.
[0124] Other experimental steps and conditions are the same as those in Example 1.
[0125] Comparative Example 1
[0126] Compared with Example 3, the difference is that no coconut fiber charcoal is added.
[0127] Example 4
[0128] Compared with Example 3, the difference is that 10 parts by weight of wrinkled graphene-coated TiO2@activated carbon prepared in Preparation Example 1 is added.
[0129] Example 5
[0130] Compared with Example 3, the difference is that 10 parts by weight of the wrinkled graphene-coated TiO2@activated carbon prepared in Preparation Example 2 are used instead of 7 parts by weight of the wrinkled graphene-coated TiO2@activated carbon prepared in Preparation Example 1.
[0131] Example 6
[0132] Compared with Example 3, the difference is that 7 parts by weight of the wrinkled graphene-coated TiO2@activated carbon prepared in Preparation Example 2 is used instead of 7 parts by weight of the wrinkled graphene-coated TiO2@activated carbon prepared in Preparation Example 1.
[0133] Example 7
[0134] Compared with Example 3, the difference is that 10 parts by weight of the wrinkled graphene-coated TiO2@activated carbon prepared in Preparation Example 3 are used instead of 7 parts by weight of the wrinkled graphene-coated TiO2@activated carbon prepared in Preparation Example 1.
[0135] Comparative Example 2
[0136] Compared with Example 6, the difference is that the wrinkled graphene-coated activated carbon prepared in Comparative Preparation Example 1 is used to replace the wrinkled graphene-coated TiO2@activated carbon prepared in Preparation Example 1.
[0137] Comparative Example 3
[0138] Compared with Example 6, the difference is that the wrinkled graphene-coated TiO2@activated carbon prepared in Comparative Preparation Example 2 is used to replace the wrinkled graphene-coated TiO2@activated carbon prepared in Preparation Example 1.
[0139] Comparative Example 4
[0140] Compared with Example 6, the difference is that the TiO2@activated carbon prepared in Comparative Preparation Example 3 is used to replace the wrinkled graphene-coated TiO2@activated carbon prepared in Preparation Example 1.
[0141] Comparative Example 5
[0142] Compared with Example 6, the difference is that the wrinkled graphene oxide-coated TiO2@activated carbon prepared in Comparative Preparation Example 4 is used to replace the wrinkled graphene-coated TiO2@activated carbon prepared in Preparation Example 1.
[0143] Test Example 1
[0144] The compressive strength and purification efficiency of the indoor air purification aerated concrete blocks prepared in Examples 1-6 and Comparative Examples 1-5 were tested.
[0145] The compressive strength of masonry blocks is determined in accordance with the national standard GB / T 11969-2020 "Test method for properties of autoclaved aerated concrete".
[0146] The formaldehyde concentration is determined in accordance with the national standard GB / T 18883-2022 "Indoor Air Quality Standard".
[0147] The results are shown in Table 1.
[0148] Table 1 Strength and formaldehyde purification efficiency results of lightweight materials obtained from different comparative examples and examples
[0149] <![CDATA[Density / kg / m 3 > Compressive strength / MPa Formaldehyde purification efficiency / % Example 1 643 5.65 85 Example 2 664 5.85 81 Example 3 640 5.62 87 Example 4 636 5.72 89 Example 5 639 5.75 89 Example 6 639 5.65 88 Example 7 636 5.75 90 Comparative Example 1 698 6.22 32 Comparative Example 2 649 5.02 45 Comparative Example 3 642 5.35 74 Comparative Example 4 650 5.62 70 Comparative Example 5 645 5.22 78
[0150] It can be seen from the above table that the indoor air purification aerated concrete block prepared by the present invention has good compressive strength and formaldehyde purification efficiency.
[0151] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An aerated concrete block for purifying indoor air, characterized in that: The invention is prepared from the following raw materials by weight: 10-40 parts of titanium gypsum, 10-20 parts of silicate cement, 2-10 parts of aluminate cement, 10-20 parts of quicklime, 20-60 parts of fly ash, 1-2 parts of aluminum powder, 5-20 parts of quartz sand, 0.5-10 parts of coconut fiber carbon, 0.5-2 parts of foam stabilizer, 0.2-2 parts of water reducer, 40-45 parts of water, and 5-10 parts of modified activated carbon; The modified activated carbon is wrinkled graphene-coated TiO2@activated carbon; the preparation method of the wrinkled graphene-coated TiO2@activated carbon is as follows: S1. Soaking the activated carbon in an alkali solution, filtering, washing, drying, and ball milling to obtain a pretreated activated carbon powder; S2. The tetrabutyl titanate, ethanol and water are mixed to obtain a titanium sol; the mass ratio of tetrabutyl titanate, ethanol and water is 10-15:70-100:7-12; S3. The pretreated activated carbon powder obtained in step S1 is added to the titanium sol obtained in step S2, stirred and mixed evenly, calcined, and ball-milled to obtain TiO2@ activated carbon; the mass ratio of the pretreated activated carbon powder to the titanium sol is 10:12-15; S4. The TiO2@ activated carbon obtained in step S3 is added to the graphene oxide aqueous solution, stirred and mixed evenly, and spray-dried to obtain wrinkled graphene oxide-coated TiO2@ activated carbon; the concentration of graphene oxide in the graphene oxide aqueous solution is 10-15wt%, and the mass ratio of the TiO2@ activated carbon to the graphene oxide aqueous solution is 1:5-10; S5. Add the wrinkled graphene oxide coated TiO2@activated carbon obtained in step S4 into water, add ammonia water and hydrazine hydrate, heat and stir to react, filter, wash, and dry to obtain wrinkled graphene coated TiO2@activated carbon.
2. The indoor air purification aerated concrete block according to claim 1, characterized in that: The foam stabilizer is selected from one or more of polyacrylamide, polyvinyl alcohol, sodium sulfate of fatty alcohol polyoxyethylene ether, dodecyl dimethyl amine oxide, and alkyl alcohol amide; the water reducer is selected from one or more of naphthalene water reducer, aliphatic water reducer, amino water reducer, and polycarboxylic acid water reducer.
3. The indoor air purification aerated concrete block according to claim 1, characterized in that: The alkali solution in step S1 is a 5-10wt% NaOH or KOH solution, the solid-liquid ratio of the activated carbon to the alkali solution is 1:5-10g / mL, and the ball milling time is 2-4h.
4. The indoor air purification aerated concrete block according to claim 1, characterized in that: In step S3, the calcination temperature is 400-500°C, the time is 2-4 hours, and the ball milling time is 1-2 hours.
5. The indoor air purification aerated concrete block according to claim 1, characterized in that: In step S4, the spray drying conditions are as follows: the air inlet temperature is 80-100°C, the air outlet temperature is 30-80°C, and the evaporated water volume is 1500-2000 mL / h.
6. The indoor air purification aerated concrete block according to claim 1, characterized in that: In step S5, the mass ratio of the wrinkled graphene oxide coated TiO2@activated carbon, ammonia water and hydrazine hydrate is 10:3-5:1-3, the concentration of ammonia water is 25-27wt%, the temperature of the heating and stirring reaction is 75-85°C, and the time is 1-2h.
7. A method for preparing an aerated concrete block for purifying indoor air as claimed in claim 1 or 2, characterized in that: The following steps are involved: 1) Mixing silicate cement, aluminate cement, quicklime, fly ash, modified activated carbon and quartz sand uniformly to obtain powder; 2) mixing aluminum powder and 1-2 parts of water and then ultrasonically mixing to obtain a suspension 1; 3) mixing titanium gypsum and 20-30 parts of water and performing wet grinding to obtain slurry 1; 4) Add the powder, slurry 1, water reducing agent and remaining water into a blender and mix well to obtain slurry 2; 5) adding the suspension 1, the foam stabilizer and the coconut fiber charcoal into the slurry 2 and continuing to stir and mix in a blender to obtain a slurry 3; 6) injecting the slurry 3 into a mold for forming, curing in a curing box, demoulding, and continuing curing for a specified time, and then placing the hardened body into a cement autoclave to obtain a porous lightweight material; 7) The porous lightweight material is used to build a wall, and a layer of environmentally friendly water-based paint is applied on the surface of the wall to obtain aerated concrete blocks that purify indoor air.
Citation Information
Patent Citations
Preparation method of autoclaved aerated concrete based on titanium gypsum base
CN112125598A
Environment-friendly wall coating for building and preparation method of environment-friendly wall coating
CN113736293A
High-adsorption carbon-plastic composite material manufacturing technology
CN109135306A
Manufacturing process of autoclaved aerated concrete block
CN111943617A
Graphene composite PE material and preparation method thereof
CN114163712A